2017
DOI: 10.1001/jamaneurol.2017.2492
|View full text |Cite
|
Sign up to set email alerts
|

Association of Prognostic Factors and Immunosuppressive Treatment With Long-term Outcomes in Neurosarcoidosis

Abstract: IMPORTANCE Prognostic factors are lacking in neurosarcoidosis (NS), and the association of immunosuppressive treatments with outcomes are unclear.OBJECTIVES To identify prognostic factors of and analyze the association of immunosuppressive treatment with relapse of NS. DESIGN, SETTING, AND PARTICIPANTSIn this retrospective study, a cohort of 234 patients fulfilled the diagnostic criteria for NS in a tertiary referral center in Paris, France, from January 1, 1990, through December 31, 2015. The median follow-up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
67
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(74 citation statements)
references
References 14 publications
1
67
0
3
Order By: Relevance
“…It is highly likely that these differences can be explained by the small sample sizes and mainly retrospective design of these previous studies [9], and by the tertiary setting of our neurosarcoidosis population. A comparison between our results and those reported from other referral centres showed that results were similar [16,24,33].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…It is highly likely that these differences can be explained by the small sample sizes and mainly retrospective design of these previous studies [9], and by the tertiary setting of our neurosarcoidosis population. A comparison between our results and those reported from other referral centres showed that results were similar [16,24,33].…”
Section: Discussionsupporting
confidence: 89%
“…Neurosarcoidosis can involve any part of the nervous system, causing a variety of neurological symptoms. A meta-analysis showed that the most common manifestations of neurosarcoidosis were cranial nerve dysfunctions and myelopathy [16,17]. Since neurologic involvement is the first presenting symptom in 50-70% of the neurosarcoidosis patients, and 52% of the patients have isolated neurosarcoidosis without systemic involvement [18][19][20][21][22], it can be difficult to diagnose.…”
Section: Introductionmentioning
confidence: 99%
“…23 Moreover, compared with many pathologies affecting the spinal cord, neurosarcoidosis is a treatable condition-often responding well to steroids, immunosuppressive therapies, or certain monoclonal antibodies. 24,25 Of interest, although disability status of SAM in a subset of patients in our cohort showed improvement in 52% after 1-year follow-up, almost 26% had worsening disability, a finding that may reflect the refractory and aggressive neuroinflammatory process in SAM in some patients or the delay in diagnosis and treatment that may also affect the overall outcome. Thus, it is essential for clinicians to recognize the clinical characteristics, CSF, and imaging findings associated with this disorder.…”
Section: Discussionmentioning
confidence: 76%
“…1 Neurologic manifestations occur in 5% of patients, and mortality can be as high as 11% in the 10 years after initial diagnosis. 2,3 Neurosarcoidosis has a predilection for perivascular dissemination but can also lead to parenchymal, leptomeningeal, or pachymeningeal disease and may result in a granulomatous angiitis. 4,5 CNS complications can be diverse and are a function of the nature and extent of tissues involved.…”
mentioning
confidence: 99%